A Comprehensive Functional Analysis of NTRK1 Missense Mutations Causing Hereditary Sensory and Autonomic Neuropathy Type IV (HSAN IV). Issue 1 (26th November 2016) - Shaikh, Samiha S.; Chen, Ya‐Chun; Halsall, Sally‐Anne; Nahorski, Michael S.; Omoto, Kiyoyuki; Young, Gareth T.; Phelan, Anne; Woods, Christopher Geoffrey
Abstract : Fact : Mutations in the Neurotrophic Receptor Tyrosine Kinase 1 (TRKA) can cause Congenital Painlessness. Findings : We found that pathogenic mutations operate by multiple mechanisms; and no one functional assay of TRKA detected all. Beware : One mutation, predicted pathogenic by all algorithms, was benign. ABSTRACT: Hereditary sensory and autonomic neuropathy type IV (HSAN IV) is an autosomal recessive disorder characterized by a complete lack of pain perception and anhidrosis. Here, we studied a cohort of seven patients with HSAN IV and describe a comprehensive functional analysis of seven novel NTRK1 missense mutations, c.1550G >A, c.1565G >A, c.1970T >C, c.2096T >C, c.2254T >A, c.2288G >C, and c.2311C >T, corresponding to p.G517E, p.G522E, p.L657P, p.I699T, p.C752S, p.C763S, and p.R771C, all of which were predicted pathogenic by in silico analysis. The results allowed us to assess the pathogenicity of each mutation and to gain novel insights into tropomyosin receptor kinase A (TRKA) downstream signaling. Each mutation was systematically analyzed for TRKA glycosylation states, intracellular and cell membrane expression patterns, nerve growth factor stimulated TRKA autophosphorylation, TRKA‐Y496 phosphorylation, PLCγ activity, and neurite outgrowth. We showed a diverse range of functional effects: one mutation appeared fully functional, another had partial activity in all assays, one mutation affected only the PLCγ pathway and four mutations were proved null in all assays. Thus, we conclude that complete abolition of TRKA kinase activity is not the only pathogenic mechanism underlying HSAN IV. By corollary, the assessment of the clinical pathogenicity of HSAN IV mutations is more complex than initially predicted and requires a multifaceted approach.